DAMPAK INFEKSI COVID-19 TERHADAP SIKLUS MENSTRUASI PADA PENYINTAS COVID-19 - Maulida, Ika; Bustamam, Nurfitri; Astari, Riezky Valentina; Lardo, Soroy (Poltekkes Kemenkes Bandung, 2024)
The study results of 2020 reported that as many as 16% of COVID-19 survivors experience changes in their menstrual cycles. This study aimed to describe the menstruation cycle among COVID-19 survivors at The Faculty of Medicine, University Pembangunan Nasional “Veteran” Jakarta. This is an analytical study using a retrospective design. The sample size consisted of 32 subjects who met the criteria of being confirmed with COVID-19 within the past year, aged 18-24 years, normoweight, unmarried, and without a history of illness or the use of hormonal contraception that affects the menstrual cycle. Data was collected using a questionnaire. The results of the univariate analysis indicate that out of the subjects, 18 (56.3%) had received three doses of vaccination, 21 (65.6%) had received the first and second doses of the Sinovac vaccine, 31 (96.9%) experienced mild symptoms (home isolation) during the COVID-19 infection, and 9 (28.1%) had been infected with COVID-19 twice. Changes in menstrual cycles experienced by subjects 0-6 months after being infected with COVID-19 included two subjects with prolonged cycles, three subjects with shortened cycles, one subject with decreased menstrual blood volume, one subject with increased menstrual duration, five subjects experiencing menstrual pain, and two subjects experiencing bleeding between two cycles. A total of 8 subjects reported that these changes in menstrual cycles were recurring. The Chi-square exact test result indicates there was a relationship between the frequency of COVID-19 infection and the number of menstrual cycle changes (p = 0.022).